Pengaruh Kecendrungan Berpikir Kritis Terhadap Kemampuan Generalisasi Matematis Padamateri Barisan Dan Deret Siswa Kelas XII Sma Negeri 1 Narmada - Anas Usman Husnuddu’a; Ketut Sarjana; Eka Kurniawan; Harry Soeprianto (Griya Journal of Mathematics Education and Application, 2022)
The tendency to think critically is one of the main objectives of learning in the 2013 curriculum which expects students to have character. The objectives to be achieved in this study are to determine the effect of students' critical thinking tendencies on mathematical generalization abilities in class XII students of SMA Negeri 1 Narmada Based on the results of descriptive statistical analysis, there are 50.0% of students categorized as very good, 28.125% of students categorized as good, and 21.875% of students categorized as good enough. And for mathematical generalization ability, there are 46.875% students categorized very well, 50.0% students are categorized as good, and 3.125% students are categorized as good enough. The conclusion of this study shows that there is a significant influence of the tendency to think critically on the generalization ability of the students of SMA Negeri 1 Narmada in the academic year of 2022/2023.